Si modified Ge-10 cluster: the preparation and characterization of single crystal Na-4(Ge,Si)(9)O-20 - Xiao, P; Ren, T; Wang, Z; Christensen, K (2010)
A Si modified Ge10 cluster with structure Na4(Ge,Si) 9O20 (denoted as HUT-1) was synthesized by hydrothermal synthesis at 160 °C with a sodium silicate source. The compound was characterized by single crystal, powder X-ray diffraction and TGA-DSC analysis. HUT-1 crystallizes in space group I41 (80) with calculated unit cell (a=14.966(5) Å, c=7.343(2) Å, V=1644.8(9) Å3), which has the same structure as Na4Ge9O20. HUT-1 has a high Si/Ge ratio with an approximate formula of NaM 4Ge7.68Si1.32O20. Single crystal X-ray structure refinements together with results from X-ray powder diffraction (XRPD) confirm the occupancy of Si at two tetrahedral sites. © 2010 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.